The Institution of the Duel in Arthur Schnitzler's Dramas and Prose works with A Translation into English of the Novella Leutnant Gustl - Mabson, Marguerite (My University, 1983)
This thesis discusses the Institution of the Duel in the dramas and prose works of Arthur Schitzler, and presents a translation into English of the novella Leutnant Gustl.
A preliminary chapter provides short biographical details and outlines the general cultural, political and social atmosphere of the times.
The concluding chapter discusses the translation and points out certain specific problems.
All quotations from Schintzler's Dramas and Prose Works are from the following editions:
Arthur Schnitzler, Gesammelte Werke: Die dramatische Werke.
2 vols. Frankfurt am Main: Fischer Verlag, 1962.
Arthur Schnitzler, Gesammelte Werke: Die erzáhlenden Schriften.
2 vols. Frankfurt am Main: Fischer Verlag, 1962.
Keywords: German; German Language and Literature; German Language and Literature